Poverty trends in villages affected by land-based investments in rural Laos. (November 2020) - Nanhthavong, Vong; Epprecht, Michael; Hett, Cornelia; Zaehringer, Julie G.; Messerli, Peter
Abstract: This paper contributes to debates on the implications of land-based investments on local livelihoods in the Global South. Drawing on a comprehensive national dataset on land concessions in Laos, and 2005 and 2015 village-level poverty rates, we examine the association between land-based investments and poverty at the village level in Lao rural areas. Results outline contexts in which land-based investments have either positive or adverse association with village-level poverty change rates; they also reveal factors that determine village-level poverty reduction in Laos. Our results suggest that poverty rates in villages affected by land-based investments decreased significantly between 2005 and 2015, following the national trend in Laos. However, in cases where land-based investments caused more farmland loss, poverty reduction was low or poverty rates increased over this period. Results further reveal that land-based investments implemented in more remote areas or poorer villages had a stronger association with poverty reduction. However, poverty was not a central consideration for the establishment of land-based investments. Our findings fill an important gap, providing a middle-level analysis from which grounded observations are analyzed alongside national trends. Highlights: Poverty rates in affected villages decreased between 2005 and 2015, consistent with Laos' national decrease in poverty. However, in villages that lost more land in these deals, the poverty rate increased between 2005 and 2015. Deals in poorer areas have stronger association with poverty reduction, but most deals targeted less poor areas. Temporal-statistical and qualitative analyses reveal contexts where deals positively or negatively affect poverty change.